1991
DOI: 10.1073/pnas.88.10.4195
|View full text |Cite
|
Sign up to set email alerts
|

The protein-folding problem: the native fold determines packing, but does packing determine the native fold?

Abstract: A globular protein adopts its native threedimensional structure spontaneously under physiological conditions. This structure is specified by a stereochemical code embedded within the amino acid sequence of that protein.Elucidation of this code is a major, unsolved challenge, known as the protein-folding problem. A critical aspect of the code is thought to involve molecular packing. Globular proteins have high packing densities, a consequence of the fact that residue side chains within the molecular interior fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 54 publications
5
62
0
Order By: Relevance
“…Side chains in this simple model of nuts and bolts packing (1) strongly oppose folding, compared to the linear chain; (2) only freeze completely into place and lose much entropy in the final approach to maximum compactness; (3) give rise to different contact frequencies among and between side chains and main chain in open states; (4) give rise to distributions of the different contact types in compact states similar to those observed in the PDB; (5) have no steric complementarities and therefore predict tolerance to mutations and relatively random distributions of mutually buried areas as observed by Behe et al (1991); and (6) do not by themselves lead to an entropy barrier that could account for the 2-state thermodynamics of protein folding. The SCM is simple enough to permit explorations of open conformations without approximation, including main-chain degrees of freedom, and to predict how configurational freedom and patterns of intrachain contacts depend on chain density.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Side chains in this simple model of nuts and bolts packing (1) strongly oppose folding, compared to the linear chain; (2) only freeze completely into place and lose much entropy in the final approach to maximum compactness; (3) give rise to different contact frequencies among and between side chains and main chain in open states; (4) give rise to distributions of the different contact types in compact states similar to those observed in the PDB; (5) have no steric complementarities and therefore predict tolerance to mutations and relatively random distributions of mutually buried areas as observed by Behe et al (1991); and (6) do not by themselves lead to an entropy barrier that could account for the 2-state thermodynamics of protein folding. The SCM is simple enough to permit explorations of open conformations without approximation, including main-chain degrees of freedom, and to predict how configurational freedom and patterns of intrachain contacts depend on chain density.…”
Section: Discussionmentioning
confidence: 90%
“…There is further evidence in protein dynamics studies for the flexibility of protein interiors: small molecules rapidly diffuse to buried residues (Gurd & Rothgeb, 1979;Karplus & McCammon, 1981), and aromatic rings rotate with low activation energy barriers (Wiithrich & Wagner, 1978). Finally, studies of protein native structures show that neighboring core side chains have little or no tendency toward specific preferred mutually buried areas (Behe et al, 1991), and little preference for particular relative orientations of spatially neighboring hydrophobic side chains (Singh & Thornton, 1990, 1992. In these respects side-chain organization does not resemble the packing of a jigsaw puzzle.…”
Section: Views Of Packing In Proteinsmentioning
confidence: 99%
“…This should occur in a correlated fashion with good sidechain packing of the sandwiched hydrophobics-residues. Behe et al (1991) reported that hydrophobic interactions alone provide insufficient directionality and specificity for native-like folding. In ppep-4, the interfacial p-strand hydrogen bonds could direct the uniqueness of the fold.…”
Section: Discussionmentioning
confidence: 99%
“…The role of packing interactions in the stability of proteins has been widely debated (43)(44)(45). Although hydrophobic interactions are considered the major determinant of protein stability, the observation of a state in which the core is loosely packed but dry highlights the importance of packing interactions for the stability of the protein fold.…”
Section: Discussionmentioning
confidence: 99%